The Influence Of Public Trust And Tax Socialization On Tax Compliance Of Msme Taxpayers (Case Study On Individual Taxpayers At Kpp Pratama Bandung Bojonagara For The 2023 Period) - Radhya Yudiastama; Galuh Tresna Murti (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Taxpayer compliance is a key factor in optimizing state revenue. However, the compliance level of MSME taxpayers in Indonesia, including those registered at KPP Pratama Bandung Bojonagara, remains relatively low despite the continuous increase in the number of taxpayers. This condition indicates a gap between potential revenue and the realization of Annual Tax Return (SPT) reporting. This study aims to examine the effect of Public Trust and Tax Socialization on the compliance of MSME individual taxpayers who are non-employees and registered at KPP Pratama Bandung Bojonagara in 2023. The research employed a quantitative approach with descriptive and verificative methods. The population consisted of more than twenty-two thousand taxpayers, with a sample of one hundred respondents determined using Slovin’s formula. Primary data were collected through questionnaires, while secondary data were obtained from official documentation of the tax office. The data analysis involved validity and reliability tests, classical assumption tests, multiple linear regression, coefficient of determination, F-test, and t-test. The findings reveal that Public Trust and Tax Socialization simultaneously have a positive and significant effect on taxpayer compliance. Partially, both variables also show a positive and significant effect. The coefficient of determination indicates that Public Trust and Tax Socialization explain only a part of taxpayer compliance, while the remaining portion is influenced by other factors beyond this study